DIVERSIFIKASI PRODUK PENGANAN BERBASIS TEPUNG MOCAF (MODIFIED CASSAVA FLOUR) DI INDUSTRI MIKRO NONAD, ACEH BESAR - Yusriana, Yusriana; Rozali, Zalniati Fonna; Rohaya, Syarifah; Meldasari, Yanti (Universitas Syiah Kuala, 2025)
Utilizing local food ingredients is an important strategy in strengthening food security and reducing dependence on imported ingredients. Mocaf (modified cassava flour) is an alternative substitute for wheat flour derived from processed cassava through a fermentation process. This community service activity aims to increase the capacity of product innovation in the Nonad micro industry, Aceh Besar, through diversification of mocaf flour-based snacks. This service activity is carried out through training methods, technical assistance, and product trials. In addition, this activity also provides an introduction to the equipment and packaging that will be used to produce several snack products such as pizza cakes and sponge cakes that are worthy in taste and appearance. The results of the activity showed high enthusiasm from partners in participating in the training and applying the manufacture of pizza and sponge cakes with the addition of mocaf flour, so that it is expected to improve quality and expand market access.